Old field restoration : vegetation response to soil changes and restoration efforts in Western Cape Lowlands - Memiaghe, Herve Roland (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--Stellenbosch University, 2008.